Persepsi Mahasiswa tentang Penggunaan Artificial Intelligence Quillbot dalam Mengatasi Plagiarisme dan Kesadaran Etika Akademik Mahasiswa - Luthfiah, Naurah; Salminawati, Salminawati; Dahlan, Zaini (Jayapangus Press, 2024)
This research aims to analyze student perceptions regarding the use of artificial intelligence quillbot in overcoming plagiarism and students' awareness of academic ethics. This type of research is qualitative with a case study approach. Data collection uses observation, questionnaires, interviews and document studies. Data analysis is carried out continuously, starting from data reduction to drawing conclusions. The research results show that the use of Artificial Intelligence QuillBot in overcoming plagiarism in the Islamic Religious Education Study Program at the State Islamic University of North Sumatra is highlighted through two approaches, namely first, the resource person supports the use of the plagiarism checker feature as a solution for detecting plagiarism in their scientific work. They consider QuillBot not only as a tool, but also as a necessity in completing course assignments well, especially because a low level of plagiarism is expected. Second, QuillBot's ability to paraphrase automatically can simplify the process of avoiding plagiarism, reduce the risk of using unoriginal content, and increase the authenticity of scientific work. Some students consider their awareness of academic ethics to be good, showing progress in respecting the principles of academic integrity, such as avoiding plagiarism and stating sources clearly. However, there is still an opinion that awareness of academic ethics still needs to be increased because there are still many students who are less aware of the importance of academic integrity, especially regarding the issue of plagiarism.